Answer:
x = 7y
Step-by-step explanation:
x+8y/4=9y
Multiply each side by 4 to get rid of the fractions
4(x+8y/4)=9y*4
Distribute
4x +8y = 36y
Subtract 8y from each side
4x +8y-8y = 36y-8y
4x = 28y
Divide each side by 4
4x/4 = 28y/4
x = 7y
<h2><u>Solution</u></h2>
![\frac{4}{3} - 2 \\ \\ = \frac{4 - 6}{ 3} \\ \\ = \frac{ - 2}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B3%7D%20%20-%202%20%5C%5C%20%20%5C%5C%20%20%20%3D%20%5Cfrac%7B4%20-%206%7D%7B%203%7D%20%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%20-%202%7D%7B3%7D%20)
<h3>Hope This Helps You ❤️</h3>
Answer:
6 - 5d is an expression equivalent to -5d + 6 using the commutative Property of Addition.
Step-by-step explanation:
Commutative Property of Addition
We know that we can add two numbers in any order.
For example,
Let 'a' and 'b' be two numbers.
We can add 'a' and 'b' numbers in any order, such as
a + b = b + a
Thus,
a + b = b + a is represented using the commutative Property of Addition.
In our case,
-5d + 6 can be written or represented using the commutative Property of Addition, such as
-5d + 6 = 6 - 5d
It is clear that -5d + 6 can be written in any order such as 6 - 5d.
In other words, 6 - 5d is an expression equivalent to -5d + 6 using the commutative Property of Addition.
Therefore, 6 - 5d is an expression equivalent to -5d + 6 using the commutative Property of Addition.
Answer:
what I dont even know whT your talking about. could you please explain your question a bit more?? then maybe I could help you out
Answer:
b & c for sure
Step-by-step explanation:
............